2. AWARENESS OF THE USE OF HALAL LABELS ON PRODUCTS AMONG MUSLIM CONSUMERS IN MIRI, SARAWAK: , consumer behavior, halal awareness, religiosity - Miasin, Suhaimah; Abdul Rasol, Lokman; Ibrahim, Nurshahira; Ibrahim, Rasyad Afif; Md Baharudin, Md Hamzaimi Azrol; Mahmud, Maziah (Journal of Islamic, Social, Economics and Development, 2024)
This study investigates Muslim consumers' perceptions of halal food products and logos in Miri, Sarawak, highlighting the high level of awareness and sensitivity towards the halal logo among consumers. The research supports the extended Theory of Planned Behavior (TPB), emphasizing the role of religiosity and halal awareness in shaping consumer behavior. A quantitative evaluation methodology was employed, with data collected through questionnaires distributed to Muslim consumers in both urban and rural areas of Miri. The purposive sampling method targeted a relevant sample of 110 participants, and data analysis was conducted using SPSS software to reveal significant trends and insights. The findings underscore the importance of maintaining rigorous halal certification processes and suggest practical applications for industry stakeholders and policymakers, including enhancing consumer education, improving certification transparency through advanced technologies like blockchain, and fostering collaboration for standardized global halal certification processes. Addressing the misuse of halal logos through stringent legal measures and public awareness campaigns, as well as engaging with local communities and religious institutions, are also recommended. Despite limitations such as potential biases in self-reported data and a sample size that may not fully represent the broader population, the study provides a solid foundation for future research. Future studies should aim to address these limitations and explore new avenues for enhancing the transparency and reliability of halal certification processes. The study's insights contribute to the broader discourse on halal food governance, consumer education, and the development of more effective halal certification systems.